2019
DOI: 10.1111/1750-3841.14958
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Buckwheat Fermented Milk Combined with High‐Fat Diet on Rats’ Gut Microbiota and Short‐Chain Fatty Acids

Abstract: The aim of this study was to evaluate the effect of buckwheat fermented milk on intestinal flora and short-chain fatty acids (SCFAs) of rats fed a high-fat diet (HFD). Buckwheat fermented milk was made with Lactobacillus plantarum ST-Ⅲ, Lactobacillus bulgaricus, and Streptococcus thermophilus. Thirty-six males C57BL/6 rats (aged 3 weeks and with 9 to 12 g weight) were subjected to a 2-week adaptive period on a normal diet. After a week of acclimatization, the rats were randomly divided into three groups with 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Pro-inflammatory factors in the stomach tissue of buckwheat-fed mice were similar to mice that received a low salt diet [ 32 ]. When comparing rats on a high-fat diet to those fed with a normal diet, a high-fat diet with fermented milk and a high-fat diet with buckwheat for four weeks led to lower pro-inflammatory markers in the colon [ 34 ]. Finally, in the study that included piglets [ 31 ], buckwheat, in combination with probiotics, was unable to influence the intestinal histomorphology and induction of the mucosal immune system among piglets.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pro-inflammatory factors in the stomach tissue of buckwheat-fed mice were similar to mice that received a low salt diet [ 32 ]. When comparing rats on a high-fat diet to those fed with a normal diet, a high-fat diet with fermented milk and a high-fat diet with buckwheat for four weeks led to lower pro-inflammatory markers in the colon [ 34 ]. Finally, in the study that included piglets [ 31 ], buckwheat, in combination with probiotics, was unable to influence the intestinal histomorphology and induction of the mucosal immune system among piglets.…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies applied Tartary buckwheat and reported differences in the animal fecal microbiome in comparison to a high-fat diet [ 7 , 34 , 44 , 45 , 46 , 48 , 49 , 50 ] and basal diet [ 53 ]. In Supplemental Figure S2 , we summarized the findings on differences in GI microbiota from animal studies using Tartary buckwheat as an intervention.…”
Section: Resultsmentioning
confidence: 99%
“…When intestinal microbiota decompose dietary fiber, they produce a variety of metabolites, including SCFAs ingested by the epithelial cells of the colon, which affect the physiological processes of the host [58]. Intestinal microflora promotes α-syn-mediated dyskinesia and brain-related pathological processes by producing SCFAs.…”
Section: Gut Flora and Parkinsonmentioning
confidence: 99%
“…The buckwheat fermented milk remarkably repressed the increases in LPS levels in the colon and the antioxidant indexes in HFD-fed rats. In addition, buckwheat fermented milk significantly enhanced the abundance of the genus Akkermansia and decreased the abundance of the Lachnospiraceae family [56]. It has been proved that the species belonging to Lachnospiraceae are linked to the development of obesity and type 2 diabetes in ob/ob rats, whereas Akkermansia, belonging to Verrucomicrobia, plays an important role in treating obesity, inflammation, type 2 diabetes, and metabolic syndrome [57,58].…”
Section: Hyperlipidemiamentioning
confidence: 99%